Dye coupling of horizontal cells in the primate retina - Pan, Feng; Massey, Stephen C. (Frontiers in Ophthalmology, 2023)
In the monkey retina, there are two distinct types of axon-bearing horizontal cells, known as H1 and H2 horizontal cells. The cell bodies were prelabeled using DAPI, and both types were filled with Neurobiotin to reveal coupling, cellular details and photoreceptor contacts. Confocal analysis of H1 and H2 horizontal cells was used to assess the colocalization of terminal dendrites with glutamate receptors at cone pedicles.After filling H1 somas, a large, coupled mosaic of H1 cells was labeled. The dendritic terminals of H1 cells contacted red/green cone pedicles with occasional sparse contacts with blue cone pedicles. H2 cells were also dye-coupled. They had larger dendritic fields and a lower density. The dendritic terminals of H2 cells preferentially contacted blue cone pedicles, but there were still additional contacts with nearly all cones within the dendritic field. Red/green cones account for 99% of the input to H1 HCs whereas H2 HCs receive a more balanced input, 58% red/green and 42% blue. These observations confirm earlier work on primate horizontal cells (Dacey et al., 1996;Goodchild et al., 1996). Both H1 and H2 horizontal cells were axon-bearing. H1 axon terminals (H1 ATs) were independently coupled and contacted rod spherules exclusively.In contrast, H2 axon terminals contacted cones, with some preference for blue cone pedicles, as reported by Chan and Grünert (Chan and Grünert, 1998).The primate retina contains three independently coupled horizontal cell networks in the outer plexiform layer (OPL), identified as H1 and H2 somatic dendrites, and H1 ATs. At each cone pedicle, the colocalization of both H1 and H2 dendritic tips with GluA4 subunits close to the cone synaptic ribbons indicates that glutamate signaling from cones to H1 and H2 horizontal cells is mediated by AMPA receptors.